Effects of dynamic warm-up on lower body explosiveness among collegiate baseball players - Frantz, T. L.; Ruiz, M. D. (The Journal of Strength and Conditioning Research, 2011)
Debate exists between the benefits and effectiveness of a dynamic warm-up vs. a static warm-up. This study was conducted to compare dynamic and static warm-ups on lower body explosiveness as measured by stationary vertical jump (VJ) and standing long jump (LJ) among collegiate baseball players. Participants (n = 17; age = 19.59 ± 1.37 years) progressed through 3 different warm-ups on weekly testing dates over a 7-week period. After the warm-up routines, participants were measured for VJ height and LJ distance in centimeters. The mean jump heights for VJ were 66.49 ± 8.28 cm for dynamic, 61.42 ± 7.51 cm for static, and 62.72 ± 7.84 cm for the control condition. The mean jump distances for LJ were 231.99 ± 20.69 cm for dynamic, 219.69 ± 20.96 cm for static, and 226.46 ± 20.60 cm for the control. Results indicated that the participants jumped significantly higher in both experimental conditions while under the influence of the dynamic warm-up (VJ—F = 22.08; df = 1.33, 21.345; p < 0.00 and LJ—F = 32.20; df = 2, 32; p < 0.01). Additional LJ analysis determined that individuals jumped significantly further after no warm-up compared to after a static warm-up (-6.78, p < 0.05). Lower body explosiveness is critical in baseball and many other sports as well. The results show that dynamic warm-up increases both VJ height and LJ distance. Specifically, these findings indicate that athletes could gain nearly 2 in. on his or her vertical jump by simply switching from a static warm-up routine to a dynamic routine.